Diagnostic value of combined magnetic resonance imaging examination of brachial plexus and electrophysiological studies in multifocal motor neuropathy - Basta, Ivana; Nikolić, Ana; Apostolski, Slobodan; Lavrnić, Slobodan; Stošić-Opinćal, Tatjana; Banjalić, Sandra; Knežević-Apostolski, Slađana; Ilić, Tihomir V.; Marjanović, Ivan; Milićev, Milena; Lavrnić, Dragana (Vojnosanitetski pregled, 2014)
Background/Aim. Multifocal motor neuropathy (MMN) is an immune-mediated disorder characterised by slowly progressive asymetrical weakness of limbs without sensory loss. The objective of this study was to investigate the involvement of brachial plexus using combined cervical magnetic stimulation and magnetic resonance imaging (MRI) of plexus brachialis in patients with MMN. We payed special attention to the nerve roots forming nerves inervating weak muscles, but without detectable conduction block (CB) using conventional nerve conduction studies. Methods. Nine patients with proven MMN were included in the study. In all of them MRI of the cervical spine and brachial plexus was performed using a Siemens Avanto 1.5 T unit, applying T1 and turbo spin-echo T1 sequence, axial turbo spin-echo T2 sequence and a coronal fat-saturated turbo spin-echo T2 sequence. Results. In all the patients severe asymmetric distal weakness of muscles inervated by radial, ulnar, median and peroneal nerves was observed and the most striking presentation was bilateral wrist and finger drop. Three of them had additional proximal weakness of muscles inervated by axillar and femoral nerves. The majority of the patients had slightly increased cerebrospinal fluid (CSF) protein content. Six of the patients had positive serum polyclonal IgM anti-GM1 antibodies. Electromyoneurography (EMG) showed neurogenic changes, the most severe in distal muscles inervated by radial nerves. All the patients had persistent partial CBs outside the usual sites of nerve compression in radial, ulnar, median and peroneal nerves. In three of the patients cervical magnetic stimulation suggested proximal CBs between cervical root emergence and Erb’s point (prolonged motor root conduction time). In all the patients T2-weighted MRI revealed increased signal intensity in at least one cervical root, truncus or fasciculus of brachial plexus. Conclusion. We found clinical correlation between muscle weakness, prolonged motor root conduction time and MRI abnormalities of the brachial plexus, which was of the greatest importance in the nerves without CB inervating weak muscles.